A new and convenient method for strength evaluation of cracked cylindrical shell based on the ratio of crack tip stresses. (June 2023) - Li, Rong; Yang, Meng; Liang, Bin
Abstract: A new and convenient method for the strength evaluation of cracked cylindrical shells under diverse loadings is presented according to stress intensity factor (SIF). In the proposed method, complicated SIF computation problem is simplified by extracting and eliminating the regularly parameters, and an analogy between reference problem and unknown problem is constructed. Then, based on the developed relations, the SIFs of unknown problems can be obtained conveniently by using the reference solution and FEM stress ratios. The proposed methodology removes the common computational difficulties for calculation SIFs and its accuracy is verified against published results. The practicality of present study is studied on several examples made up of common cylindrical shells in engineering. As the authors have found similar relationships in non-thin-walled structures, the present results might be more widely applicable and useful than those listed in this paper.